(untitled) (Fiep Bulletin - online, 2014)
The Nursing Care Systematization - NCS significantly contributes to nurses characterization, enabling them to be involved in the planning, implementation and evaluation of nursing activities. Thus, the feasibility of NCS implementation in the context of primary care for bedridden elderlies has been discussed, since they represent a population that requires specific care, making them an important target for health services concerns. This study aims to evaluate the Family Health Strategy - FHS nurses’ perception of the NCS to bedridden elderlies in primary care, discuss its implementation and describe the factors that affect the use of this process. This research consists of an exploratory study with seven nurses working in the FSH in the northern region of Teresina. Data were obtained through semi-structured interviews and the method of content analysis with three categories was used: nurses’ perception of the NCS; NCS implementation and the factors that affect the NCS implementation. It was concluded that, although the NCS is considered relevant by all the subjects of the research, it is still dissociated from nursing practice in primary care; some factors that facilitate and hamper its implementation have been pointed out.